Phase evolution and physical properties of (l-x)BZT-xBFN Ceramic System - Maimon H. (2014)
Phase evolution and physical properties of (l-x)BZT-xBFN ceramic system were investigated to find the optimum condition for electronic applications. (l-x)BZT-xBFN powders were prepared by solid state reaction technique varying x from 0.2 to 0.8 and various sintering temperatures from 1350 °C to 1450 °C. Phase formation was investigated by X-ray diffraction technique. The XRD analysis demonstrated that with increasing BFN content in (l-X)BZT-xBFN, the structural change occurred from the tetragonal to the cubic phase at room temperature. Changes in the physical and mechanical properties were then related to this structural transformation depending on the BFN content. © 2008 Trans Tech Publications, Switzerland.